Need of Reformation in Curriculum for Improving Creativity and critical thinking in the Present Education System - Sapana Adhikari; Suman Kumar Shrestha; Jant Raj Karky (Journal of Balkumari College, 2025)
The goal of this research paper is to demonstrate that all educational systems are constructed on curriculum and to highlight the necessity for creativity and critical thinking to be updated in the current curriculum framework to reflect social trends as well as students’ needs. We live in a globalized world, which has altered our daily concerns. In such cases, the curriculum should emphasize creative learning and critical thinking. Most people think of creativity in terms of skillful outcomes such as theatrical improvisations, creative inventions, novel business concepts, and scientific breakthroughs. A creative mind is known for producing novel ideas. To think creatively, one must have a strong mental ability. Students who think creatively are more likely to learn and write creatively. As a result, creative learning assists students in surviving in today’s complex society and setting. This study highlights the importance of critical thinking in order to nurture creativity for creative learning. The technique used in this qualitative study is document analysis. The outcomes of this study indicate that traditional curricula must be revised in this age of globalization, which has globalized education. As a result, education must reflect global trends in order to foster creativity and critical thinking to improve students’ learning capacity.